Unveiling the grain boundary-related effects on the incipient plasticity and dislocation behavior in nanocrystalline CrCoNi medium-entropy alloy. (10th November 2022) - Sun, Shuo; Yang, Yang; Han, Chenxu; Sun, Guixun; Chen, Yan; Zong, Hongxiang; Hu, Jiangjiang; Han, Shuang; Liao, Xiaozhou; Ding, Xiangdong; Lian, Jianshe
Highlights: The incipient plasticity and dislocation behavior in nanocrystalline (NC) CrCoNi alloy were systematically investigated and compared with its coarse-grained (CG) counterpart and NC Ni. Multiple pop-ins appear in the P-h curves of NC and CG CrCoNi alloys but disappear in the curves of NC Ni. The incipient plasticity is mediated by dislocation nucleation in NC CrCoNi alloy but by GBs in NC Ni. Chemically complex GBs in NC CrCoNi alloy facilitate dislocation nucleation but impede dislocation propagation. Spatial restrictions from GBs in NC CrCoNi alloy induce size-dependent pop-in behaviors. Abstract: The incipient plasticity and dislocation behavior in a nanocrystalline (NC) CrCoNi medium-entropy alloy were systematically investigated in terms of pop-in events during instrumental nano-indentation tests. Quantitative statistical analysis and molecular dynamic simulations were performed to reveal the effects of grain boundaries (GBs) on initial stages of plastic deformation. Multiple pop-in events appeared during loading on the NC CrCoNi. The first pop-in that represents the initial yielding was identified to be controlled by dislocation nucleation, which is in sharp contrast to the continuous elastic-plastic transition mediated by GB mechanisms in NC pure metals. This can be attributed to the sluggish kinetics of the chemically complex GBs (CCGBs) in the NC CrCoNi that hinders diffusive GB activities but facilitates dislocation nucleation. Subsequent pop-ins were also found to be closely related to the extra dragging effects imposed by the CCGBs on dislocation propagation in the NC alloy. Moreover, the extremely small grain sizes and the consequent high-volume fraction of GBs in the NC alloy severely restrict the lengths of dislocation source and the radii of dislocation loop, giving rise to a higher critical stress, smaller activation volume and lower pop-in width as compared with its coarse-grained counterpart. These results provide new insights into the onset of nano-plasticity in concentrated multi-principal element alloys.